Audit Fee, Audit Tenure, and Audit Rotation on Audit Quality in Manufacturing Companies - Yogi Ginanjar; Wulan Riyadi; Hanikatus Sholikah (Fakultas Ekonomika dan Bisnis Universitas Majalengka, 2024)
Each company tries to compete to improve its performance by presenting qualify financial reports. Audit quality. Audit quality is influenced by audit fee, audit tenure and audit rotation which will be presented in the 2018 – 2022 period, for industrial companies on the Indonesian Stock Exchange. Dummy variable to test audit quality with the Big Four KAP and Non-Big Four KAP Auditor groups as a comparison. The natural logarithm (ln) of professional fees is used to measure audit fees. A dummy variable is also used to measure audit tenure, where 1 is for companies that have audit tenure of less than 3 years and 0 for companies that have audit tenure of more than 3 years, and audit rotation is tested using a dummy variable with 1 for rotation, 0 for companies which does not rotate. Purposive sampling was used to select samples with a sample size of 160 data. Logistic regression analysis as a method for testing hypotheses. From the test, the results showed that audit fees had a partial influence on audit quality, while audit frequency and audit rotation had no effect to audit quality.